AN AGRICULTURAL TEXT WRITTEN IN CLASSICAL OTTOMAN TURKISH: FELAHAT-NAME OF KEMANİ (PEHLEVAN) AND ITS LINGUISTIC ANALYSIS - Uğur UZUNKAYA (Fırat University, 2019)
Agriculture, which is one of the most important activities of human being has gained its importance by settled life. Agricultural activities and knowledge experienced from these activities that take their form from trial and error method has written out to transfer to the next generations. In this context, Fela?at-names especially written in the Classical Ottoman Period can be described as books that written about agricultural activities. Topics in these books are such as to shed light on all processes of agriculture. Fela?at-name of Keman? (Pehlevan) which mentioned in this study is shorter than the other books that have written in the same period. This writing has three manuscript copies; the first one is in Süleymaniye Library, the second one is in İstanbul Millet Library and the third one is in Topkapı Palace Library. In this study, Topkapı Palace copy has taken as a basis and other copies used for comparison in the linguistic analysis and preparation of the text chapter. When making the linguistic analysis, the text that written in Classical Ottoman Turkish has compared with Old Anatolian Turkish and differences between two periods have tried to be mentioned. In Classical Ottoman Turkish, vowel pointed texts that initiates phonetical and morphological features of the language of the period have decreased in number especially because of spelling’s being stereotyped. That results in studies done up to now on Classical Ottoman Turkish texts’ being published according to Old Anatolian Turkish or Turkey Turkish features. Phonetical and morphological features of this period could not be introduced clearly because of lack of grammar studies on Classical Ottoman Turkish. Solely vocabulary has been taken as a basis, it is emphasized that Arabic and Persian words are frequently used but linguistic features problem has been ignored. With the idea that while introducing the linguistic features of the period, non-literary texts are more guiding rather than literary texts with a rhetorical language that contains loanwords intensively, such a text has been selected as a subject for this study. Studies like this not only give the features of the languages of the period but also make a big contribution to the terminology of the area. As part of this study, information about Fela?at-names is given as a genre and it is tried to contribute to the exhibition of language features of the period above this Classical Ottoman text although it is small in volume. Our study co